Application of Theory of Constraints in quantity surveying firm - Norhanim Zakaria,; Azlan Shah Ali,; Teh, Yen Yi (Penerbit Universiti Kebangsaan Malaysia, 2020)
As the construction projects grow in size and complexity, the roles of Quantity Surveying (QS) firms which provide QS services getting more significant. Theory of Constraints (TOC) views every process in a system are linked and constraint needs to be identified and dealt with so that to achieve continuous improvement in the whole operation. Removing constraints are the most effective way to improve the overall system performance. As QS firm did not involve inventory, the TOC application and its impacts might be different. This research focused on how TOC approach could be applied in solving the critical constraint appeared in the QS firm. This study adopted questionnaire surveys and semi-structured interviews with QS practitioners in Kuala Lumpur, which directly involved in the management of the QS firm. Descriptive and content analysis were adopted to analyse the identified constraint. The TOC methodology used to deal with the constraint, as well as the impacts of TOC to the QS firms. It could be concluded that the most common constraint in the QS firms was the delay of project participants and substandard QS practices. Meanwhile, the concept of TOC could be applied as one of the tools in decision-making process for QS firm, especially when to dealt with constraint of the delay of project participants and providing better quality of QS services.